Heterologous Expression of Ethanol Synthesis Pathway in Glycogen Deficient Synechococcus elongatus PCC 7942 Resulted in Enhanced Production of Ethanol and Exopolysaccharides - Velmurugan, Rajendran; Incharoensakdi, Aran (Frontiers in Plant Science, 2020)
In this study, the Synechococcus elongatus PCC 7942 (hereafter S. elongatus) was engineered by the glgC knockout as well as the insertion of the pdc-adh genes from two different microorganisms. The insertion of pdc-adh genes increased the ethanol synthesis with further improvement in the productivity upon the destruction of glycogen synthesis pathway and the supplementation of cofactor. The abolition of glycogen synthesis pathway led to a considerable increase of the engineered S. elongatus metabolites involved in the ethanol synthesis pathway. Moreover, the studies on cofactor addition highlighted the importance of Mg+2, Zn+2, thiamine pyrophosphate and NADP+ in ethanol synthesis. The yields of 3856 mg/L ethanol and 109.5 µg/108 cell exopolysaccharides were obtained in the engineered S. elongatus using a photo-bioreactor under optimized conditions. This enhanced production in ethanol and exopolysaccharides are attributed to the flux of carbon from glycogen synthesis pathway and proper availability of essential components.